A candidate reference method and multiple commutable control materials for serum 25‐hydroxyvitamin D measurement. Issue 12 (13th November 2022) - Zhang, Li; Long, Qichen; Zhang, Jiangtao; Zeng, Qingzhang; Zhao, Haijian; Chen, Wenxiang; Zhang, Tianjiao; Zhang, Chuanbao
Abstract: Objectives: The aim of the current study was to establish a reliable candidate reference method for serum 25‐hydroxyvitamin D [25(OH)D] measurement and to assess the commutability of multiple control materials among liquid chromatography–tandem mass spectrometry (LC–MS/MS) methods. Methods: Serum 25‐hydroxyvitamin D2 [25(OH)D2] and 25‐hydroxyvitamin D3 [25(OH)D3] together with spiked internal standards were extracted with a one‐step approach and then analyzed by LC–MS/MS. The commutability assessment for 25(OH)D was conducted according to the Clinical and Laboratory Standards Institute (CLSI) EP14‐A3 protocol. 25(OH)D concentrations in 5 levels of unprocessed serum pools, 7 levels of serum pools spiked with 25(OH)D3 or 25(OH)D2, 3 levels of commercial control materials, 2 levels of spiked bovine serum, and 4 levels of external quality assessment (EQA) materials were measured along with 30 single‐donor samples using the candidate reference method and two routine LC–MS/MS methods. Results: The candidate reference method could separate 25(OH)D2 and 25(OH)D3 from 14 potential interfering compounds completely within a 9‐min analysis time. Good method precision was obtained, and measurement results on certified reference material NIST SRM 972a were within the uncertainty of the certified values. All candidate materials were assessed commutable for LC–MS/MS methods. Conclusions: The candidate reference method for serum 25(OH)D measurement is precise, accurate, and robust against interferences and can provide an accuracy base for routine methods. The multiple alternative control materials with commutability among LC–MS/MS methods will facilitate the further standardization for serum 25(OH)D measurement. Abstract : The developed candidate reference method for serum 25‐Hydroxyvitamin D [25(OH)D] is accurate, precise, and robust against 14 potential interfering compounds. In addition, we demonstrated the commutability of additive‐laden control materials and spiked bovine serum among 25(OH)D LC–MS/MS methods, which indicates the suitability of processed materials for use in accuracy‐based EQA programs. With advantages in storage stability, cost, and the coverage of clinically relevant intervals, these control materials will facilitate a better EQA scheme design and promote the further standardization for serum 25(OH)D measurement.